The listening bureaucrat: responsiveness in public administration - Stivers Camilla
How can good listening help public administrators be more responsive to the public? In public administration, responsibility is lauded as the essence of bureaucratic professionalism while responsiveness tends to connote inappropriate political bias. Yet too much reliance on administraors' sense of responsibility threatens democratic accountability and puts too much faith in bureaucratic expertise. This article argues that practicing responsiveness by developing the ability to listen skillfully reduces the tension between administrative effectiveness and democratic accountability. The experience of listerning involves openness, respect for difference, and reflexivity. Developing the capacity to listen well promo
Keywords: Public Administration -- U.S.A.; Bureaucrats -- U.S.A.; Civil Service -- U.S.A.